Volatile Venuses the concept of the erotic in the fiction of Anais Nin and Marguerite Duras - Vidal, Niobe Verena M. (College of Arts and Letters, University of the Philippines Diliman, 2016)
What do you mean when you say "erotic"? The concept of the erotic is linked to sexual activity - however, its exact parameters have been the subject of many debates. Art critics have proposed a general framework for this concept; but being heavily gendered, this concept involves sexual politics, and feminists have cried out that art has neglected to make space in the erotic for women to express their desires, silencing them, and rendering them as objects of pleasure. This study interrogates how selected works of fiction reinvent the erotic to incorporate the concerns of both aestheticists and feminists. It will focus on the systems of language and sexuality constructed in the texts, and will argue that the delineations provided by previous theories inhibit an inclusive feminist reading. The corpus is comprised of two short story collections by Anais Nin, Delta of Venus and Little Birds, and the novella The Lover by Marguerite Duras. Functioning on the principle that men and women are different biologically, and thus, have different experiences, realities, and languages, these works explores the philosophy of the erotic put forward by Georges Bataille, which describes the erotic as a "fascination" with difference, modifying it with a "feminine voice". In doing so, these works open up a structure of power wherein gender relations are equalized and the woman is allowed to express her desire, and own her sexuality.